Acute Traumatic Injury of the Larynx (Medicine Today, 2015)
Laryngeal trauma is rare but serious and potentially deadly injury. The prompt diagnosis and management of acute laryngeal trauma is necessary because the clinical presentation is variable depending on the location, severity, and mechanism of injury. Two case histories are presented: (1) case history No.1: a 43-year-old male, after motor vehicle accident, fractured the mid anterior thyroid cartilage and both aspects of the cricoid cartilage; however, this patient was asymptomatic from the above fractures; and (2) case history No.2: a 36-year-old male who sustained trauma to the chest, neck, and left arm after being struck by a large lead pipe which fractured the left aspect of the cricoid cartilage was symptomatic. The type rather than the severity of acute laryngeal injury and the mechanism of injury may be related to symptomatology. Acute laryngeal trauma should be recognized by trauma radiologists and emergency room physicians. Early diagnosis and management of acute laryngeal trauma may prevent unnecessary specialty consults and long-term complications.Medicine Today 2015 Vol.27(1): 36-37